Overview and recent advances in the treatment of neuroblastoma. Issue 4 (3rd April 2017) - Whittle, Sarah B.; Smith, Valeria; Doherty, Erin; Zhao, Sibo; McCarty, Scott; Zage, Peter E.
ABSTRACT: Introduction : Children with neuroblastoma have widely divergent outcomes, ranging from cure in >90% of patients with low risk disease to <50% for those with high risk disease. Recent research has shed light on the biology of neuroblastoma, allowing for more accurate risk stratification and treatment reduction in many cases, although newer treatment strategies for children with high-risk and relapsed neuroblastoma are needed to improve outcomes. Areas covered : Neuroblastoma epidemiology, diagnosis, risk stratification, and recent advances in treatment of both newly diagnosed and relapsed neuroblastoma. Expert commentary : The identification of newer tumor targets and of novel cell-mediated immunotherapy agents may lead to novel therapeutic approaches, and clinical trials for regimens designed to target individual genetic aberrations in tumors are underway. A combination of therapeutic modalities will likely be required to improve survival and cure rates for patients with high-risk neuroblastoma.